2004
DOI: 10.1016/j.jtcvs.2003.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic tracheal transplantation with omentum wrapping in the abdominal position preserves functional and structural integrity of a human tracheal allograft

Abstract: The patient is alive 31 months posttransplantation and remains in bronchiolitis obliterans syndrome stage 0. Human trachea wrapped in omentum maintains its functional and structural integrity and may be used for 2-stage allotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 19 publications
1
46
0
3
Order By: Relevance
“…31 Klepetko et al already applied human tracheal allograft with omentum wrapping to patients and reported preservation of functional and structural integrity of a human trachea. 32 These authors showed that allogeneic tissue-engineered cartilage implants, synthesized in vitro, lead to repair of tracheal defects in rabbits. A low level of inflammatory cells was detected in a minority of defect sites that were treated with cartilage grafts.…”
Section: Discussionmentioning
confidence: 99%
“…31 Klepetko et al already applied human tracheal allograft with omentum wrapping to patients and reported preservation of functional and structural integrity of a human trachea. 32 These authors showed that allogeneic tissue-engineered cartilage implants, synthesized in vitro, lead to repair of tracheal defects in rabbits. A low level of inflammatory cells was detected in a minority of defect sites that were treated with cartilage grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Klepetko et al reported preserved viability of a heterotopically revascularized allograft by wrapping it in the omentum of a patient who received a lung transplant from the same donor. Its viability was documented after 60 days (Klepetko et al, 2004).…”
Section: Reconstruction Of Long-segment Stenosis Of the Tracheamentioning
confidence: 99%
“…Clinical and experimental studies have suggested that tracheal allograft is a curative option for treating long-segment tracheal defects. [4][5][6] However, the tracheal allograft lacks an identifiable vascular pedicle that would allow direct vascular anastomosis to the blood vessels in the recipient's neck. Therefore, the safe restoration of the blood supply of the graft is a key factor to achieve successful outcomes of tracheal anastomoses.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, a 57-year-old patient who had lowsegment tracheal stenosis was alive at 31 months and achieved stage 0 bronchiolitis obliterans syndrome after a 1-stage tracheal reconstruction with the use of human trachea wrapped in the greater omentum. 4 Therefore, we decided to reconstruct a long-segment tracheal defect > 5 cm with 2-stage surgery. The allograft was revascularized by heterotopic wrapping in the recipient's greater omentum.…”
Section: Introductionmentioning
confidence: 99%